2013
DOI: 10.1093/bib/bbt073
|View full text |Cite
|
Sign up to set email alerts
|

A statistical model for QTL mapping in polysomic autotetraploids underlying double reduction

Abstract: As a group of economically important species, linkage mapping of polysomic autotetraploids, including potato, sugarcane and rose, is difficult to conduct due to their unique meiotic property of double reduction that allows sister chromatids to enter into the same gamete. We describe and assess a statistical model for mapping quantitative trait loci (QTLs) in polysomic autotetraploids. The model incorporates double reduction, built in the mixture model-based framework and implemented with the expectation-maximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Double reduction has been known about for almost a century and theories of how it should be modelled have been considered by some of the early pioneers of statistical genetics (Haldane, 1930;Mather, 1935;Fisher, 1947). It is quite common nowadays for authors to assert that double reduction is required for a complete and accurate description of autopolyploid inheritance (and by extension, that it be ignored at great peril) (Luo et al, 2004;Wu et al, 2004;Wu and Ma, 2005;Li et al, 2010;Lu et al, 2012;Xu et al, 2013). On the other hand, a number of recent reviews of allo-and autopolyploid meiosis completely fail to mention it Lloyd and Bomblies, 2016).…”
Section: Double Reductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Double reduction has been known about for almost a century and theories of how it should be modelled have been considered by some of the early pioneers of statistical genetics (Haldane, 1930;Mather, 1935;Fisher, 1947). It is quite common nowadays for authors to assert that double reduction is required for a complete and accurate description of autopolyploid inheritance (and by extension, that it be ignored at great peril) (Luo et al, 2004;Wu et al, 2004;Wu and Ma, 2005;Li et al, 2010;Lu et al, 2012;Xu et al, 2013). On the other hand, a number of recent reviews of allo-and autopolyploid meiosis completely fail to mention it Lloyd and Bomblies, 2016).…”
Section: Double Reductionmentioning
confidence: 99%
“…Previous studies have attempted to incorporate double reduction in their QTL models without providing sufficient motivation for such models apart from the completeness of their model (Xie and Xu, 2000;Li et al, 2010;Xu et al, 2013). As demonstrated here and elsewhere Zheng et al, 2016), estimation of the rates of double reduction per parental chromosome as well as the frequency of multivalent pairing are now relatively straightforward given modern high-density marker datasets.…”
Section: Double Reduction or Double Trouble?mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, an autotetraploid genotype with the 'abcd' alleles at a locus that can form six expected combinations of gametes, namely, 'ab', 'ac', 'ad', 'bc', 'bd', and 'cd', but a homozygous gamete can be generated, e.g., 'aa', 'bb', 'cc', or 'dd' (Haldane, 1930;Mather, 1935;Haynes and Douches, 1993). How to accommodate DR and its implications in a breeding program as well as the use of these marker loci in linkage mapping has been discussed for a long time (Butruille and Boiteux, 2000;Luo et al, 2000;Xu et al, 2013;Layman and Busch, 2018;Bourke et al, 2019) for some economically important species, such as potato (Bradshaw, 2007;Bourke et al, 2015) and alfalfa (Julier et al, 2003), but has not yet been reported in guinea grass.…”
Section: Introductionmentioning
confidence: 99%